2004
DOI: 10.1111/j.1778-428x.2004.tb00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Aprotinin in Cardiac Surgery

Abstract: SUMMARY Aprotinin has been studied extensively in cardiac surgery and is the only FDA approved pharmacological treatment to reduce blood transfusion in coronary artery bypass grafting (CABG) associated with cardiopulmonary bypass (CPB). Aprotinin has been evaluated in multiple double blind, placebo‐controlled, multicenter studies in cardiac surgery. In US studies, aprotinin has not been associated with an increased risk of post‐CPB myocardial infarction, graft closure, or increased risk of renal dysfunction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…One large observational study by Mangano and colleagues, 28 which found an approximate 50% relative increase in 5-year mortality with use of aprotinin, was criticized for being based on registry data and because of the possibility that selection bias (the use of aprotinin in high-risk patients) might have confounded the association between use of aprotinin and adverse effects. 7,11,12 Later studies, which appear to have been better controlled than the study by Mangano and colleagues, reported a lower but still elevated risk of death from all causes when the use of aprotinin was compared to lysine analogues or placebo. 9,10 The overall relative risk for death was similar to that observed in the BART study and to the results of the direct and indirect meta-analyses in this article.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One large observational study by Mangano and colleagues, 28 which found an approximate 50% relative increase in 5-year mortality with use of aprotinin, was criticized for being based on registry data and because of the possibility that selection bias (the use of aprotinin in high-risk patients) might have confounded the association between use of aprotinin and adverse effects. 7,11,12 Later studies, which appear to have been better controlled than the study by Mangano and colleagues, reported a lower but still elevated risk of death from all causes when the use of aprotinin was compared to lysine analogues or placebo. 9,10 The overall relative risk for death was similar to that observed in the BART study and to the results of the direct and indirect meta-analyses in this article.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] These initial studies were criticized for inadequate adjustment for known confounding factors, including the type of surgery and patient acuity. 2,11,12 However, a recent large observational study with careful propensity score matching found a 32% relative increase in hospital mortality with the use of aprotinin compared with the use of epsilon aminocaproic acid.…”
mentioning
confidence: 99%
“…The mechanism for this late mortality difference is not clear and causality cannot be inferred from this data set analysis. 12 Nevertheless, the importance of long-term data are emphasized, and distinguish this analysis from other published data on aprotinin use.…”
Section: T His Past Year Has Been a Complicated One Formentioning
confidence: 97%